1995
DOI: 10.1002/art.1780381014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patient subsets among those presumptively diagnosed with, referred, and/or followed up for systemic lupus erythematosus at a large tertiary care center

Abstract: Objective. To identify different subsets of patients from a large tertiary care center who were presumptively referred for and/or diagnosed with systemic lupus erythematosus (SLE) (or followed up).Methods. All patients who were referred, followed up, and/or diagnosed with SLE at our center, who had disease duration of 5 5 years, and who resided in Alabama, were identified and their charts reviewed and abstracted.Results. Abstracted data were reviewed by 3 rheumatologists, and patients were assigned to 1 of 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 19 publications
3
32
0
2
Order By: Relevance
“…0.001) among AfricanAmericans (37 years) compared with whites (43 years). The clinical and immunologic features of study patients are similar to those described in other SLE patient groups [21][22][23].…”
Section: Resultssupporting
confidence: 61%
“…0.001) among AfricanAmericans (37 years) compared with whites (43 years). The clinical and immunologic features of study patients are similar to those described in other SLE patient groups [21][22][23].…”
Section: Resultssupporting
confidence: 61%
“…9,10 Recently Calvo-Ale Ân et al reported a study on patients with ®bromyalgia and ANA positivity. 26 In no way, however, can our patients be considered as similar to theirs because the diagnosis of UCTD in all of our patients was based ®rmly on the presence of signs and symptoms typical of a multi-system disease, in addition to a positive serology.…”
Section: Discussionmentioning
confidence: 97%
“…Training was considered to be satisfactory after achieving interrater correlation coefficients ranging from 0.93 to 0.97 immediately after the training was completed, and ranging from 0.96 to 1.00 at 2 years into the study (21).…”
Section: Methodsmentioning
confidence: 99%